Predictive Sentencing of 16-18 Year Old Male Habitual Traffic Offenders, 1969-1975: (Oklahoma) - Whinery, Leo H. ([Verlag nicht ermittelbar], 1988)
The purpose of this study was to test the way in which different treatment modalities for teenage traffic offenders affected sentencing for subsequent traffic violations. The principal investigators focused on three things: psychological motivation or investment of emotional or psychic energy which motivates offenders to violate the law, cognitive knowledge or lack of knowledge relevant to law violation, and values relevant to a person's concern for compliance with the law. Information was collected on the personality, family, and social traits of the offenders and a control group. School, court, and police records were also reviewed. Data are provided on different treatments in terms of traffic recidivism, accident involvement, and non-traffic recidivism.